2021
DOI: 10.1186/s12960-021-00685-x
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among Syrian healthcare workers in refugee health centres

Abstract: Background Achieving universal health coverage is subject to the availability, accessibility, acceptability, and quality of health workers. Countries that host refugees and migrants, such as Turkey, must strengthen the capacity of their health systems to increase access to services, especially for refugees and migrants. The Turkish Ministry of Health adapted Syrian refugee healthcare workers in the healthcare services to boost Syrian refugees’ access to healthcare. This study aimed to assess jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
9
0
2
Order By: Relevance
“…The study had a Cronbach alpha of .86. Previous studies that have used this scale also reported excellent reliability coefficient α ranges of .85 to .91 (Deng et al, 2021; Gedif et al, 2018; Zikusooka et al, 2021).…”
Section: Methodsmentioning
confidence: 75%
“…The study had a Cronbach alpha of .86. Previous studies that have used this scale also reported excellent reliability coefficient α ranges of .85 to .91 (Deng et al, 2021; Gedif et al, 2018; Zikusooka et al, 2021).…”
Section: Methodsmentioning
confidence: 75%
“…The Minnesota Job Satisfaction Questionnaire [2], published in 1967, is a classic scale related to work improvement, and is widely used today. For example, in surveys of job satisfaction among healthcare workers [15], it is useful because it can collect a wide variety of information. Job satisfaction is also explored in the Job Satisfaction Survey (JSS) [3].…”
Section: Quality Of Worklifementioning
confidence: 99%
“…Dengan demikian, hipotesis dikonstruksi sebagai berikut: H6: Job satisfaction memediasi hubungan antara nurse practice environment dengan missed nursing care Pada hipotesis H5, di hipotesiskan bahwa nurse teamwork memiliki hubungan negatif dengan missed nursing care. Namun karena penelitian oleh Kaiser (2018) dan Zikusooka (2021) menemukan adanya hubungan positif antara nurse teamwork dan job satisfaction. Maka dikonstruksikan hipotesis sebagai berikut (Kaiser & Westers, 2018;Zikusooka et al, 2021): 1780 H7: Job satisfaction memediasi hubungan antara nurse teamwork dengan missed nursing care…”
Section: Job Burnout (Burn)unclassified
“…Namun karena penelitian oleh Kaiser (2018) dan Zikusooka (2021) menemukan adanya hubungan positif antara nurse teamwork dan job satisfaction. Maka dikonstruksikan hipotesis sebagai berikut (Kaiser & Westers, 2018;Zikusooka et al, 2021): 1780 H7: Job satisfaction memediasi hubungan antara nurse teamwork dengan missed nursing care…”
Section: Job Burnout (Burn)unclassified